Transformation of the Local Muslim Fashion Industry through E-Commerce in ASEAN - Diana Magfiroh; Komarudin Komarudin (Worldwide Research Publishing, 2025)
The Muslim fashion industry is one of the creative sectors with rapid growth in the ASEAN region, along with the increase of the Muslim middle class, internet penetration, and halal lifestyle trends. Digital transformation through e-commerce is a key catalyst that allows local brands to expand their market reach to the regional level. However, this dynamic also presents challenges in the form of cross-border regulations, logistical barriers, low digital literacy, and global competition. This study aims to analyze the transformation of the local Muslim fashion industry through e-commerce in ASEAN by emphasizing the driving and inhibiting factors, local brand adaptation strategies, as well as economic, socio-cultural, regulatory, and technological implications. The research uses a qualitative approach with a descriptive-comparative design. Data was collected through semi-structured interviews with industry players, questionnaires open to consumers, and digital observations of marketplaces and social media of Muslim fashion brands in Indonesia, Malaysia, Brunei, and Thailand. Data analysis was carried out using thematic analysis techniques and source triangulation. The findings of the study show that e-commerce is driving the significant growth of the local Muslim fashion industry, with the main adaptation strategies in the form of omnichannel marketing, influencer collaboration, culture-based storytelling, and sustainable fashion innovation. The main barriers include logistics issues (35%), cross-border regulation (30%), digital literacy (20%), and global competition (15%). Digital transformation has proven to have implications for increasing market access, strengthening ASEAN Muslim identity, and the need for harmonization of halal regulations and digital technology integration.